STABILITY ENHANCEMENT OF PROTON PUMP INHIBITOR IN STOMACH: FORMULATION AND IN-VITRO EVALUATION OF STABILIZED PROTON PUMP INHIBITOR - Pm, Aravind; Rathnanand, Mahalaxmi; C, Madhu Kumar (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Objective: The aim of the present study was to prepare a pantoprazole rosin complex tablet which would stabilize the drug in the mild acidic condition (pH 5) of the stomach during the fed state. Methods: The method of slow solvent evaporation and anti-solvent was used for the preparation of pantoprazole rosin complex. Results: The prepared pantoprazole rosin complex exhibited decreased solubility than that of pure drug. FTIR and DSC studies confirmed the formation of a complex between the pantoprazole sodium and rosin via weak ionic bonds. The in-vitro release studies of the pantoprazole rosin complex showed more than 80% release at the end of 90 minutes. Tablets were formulated using direct compression method and the prepared tablets were evaluated in-vitro. The tablets were found to be within official limits with respect to hardness, weight variation, drug content, friability etc. Conclusion: The tablet formulated with croscarmellose sodium as super disintegrant showed 97% drug release within 60 minutes. The optimized tablets were found to be stable in accelerated study conditions for a period of 1 month with respect to physical characteristics and drug content. If this process can be scaled up to manufacturing level, this technique has the potential to develop into an invaluable technology in future.Â